Agricultural workers’ labour satisfaction dependence in Russia with the use of the internet in professional activities - S. G. Bylina (Цифровая социология)
Digitalization process in the Russian agro-industrial complex is connected with an increase in the need for highly qualified personnel with competencies in the field of information and communication technologies. One of the most important incentives for consolidation highly professional personnel in rural areas is a high degree of employee satisfaction with the results of their work.   The article purpose is to determine the influence degree of the Internet use by Russian agricultural workers for professional purposes on various aspects of their labour satisfaction. Based on data from   The Russia Longitudinal Monitoring Survey – Higher School of Economics (RLMS-HSE) from 2010 to 2021, a various aspects’ comparative dynamic analysis of the labour satisfaction level of Internet users and non-users for production purposes, as well as the dynamics analysis of the Internet use by agricultural workers with the dynamics of job satisfaction level various aspects was carried out. Correlation analysis determined the influence degree of professional Internet use on the level of labour satisfaction; a dependence modeling between various aspects of labour satisfaction on the using the Internet intensity for professional purposes was accomplished. It is established that the information and communication technologies’ use increases the degree of satisfaction with various aspects of labor activity, having a special impact on professional growth opportunities. However, the growth of digital competencies raises the employees’ ambition level and, accordingly, decreases the level of his or her labour satisfaction. In order to consolidate highly professional personnel in the industry, a multi-faceted approach is needed, including all possible mechanisms of social and economic support that contribute to growth the satisfaction level of an agricultural employee with the results of his or her labor activity.